2013
DOI: 10.5617/nordina.769
|View full text |Cite
|
Sign up to set email alerts
|

Social Class in Science Class

Abstract: One of the most important aims of schooling is to give all children an equal education. Despite this, social differences continue to be reproduced and earlier studies show that there is a relationship between low socioeconomic background of students and low achievement in science education. Building upon sociological frameworks (foremost Bourdieu and Bernstein) the overall aim of this thesis was to contribute to a more complex description and analysis of inequalities in education, focusing on social class in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…In Sweden, the school’s ability to compensate for students’ background has worsened, and the parents’ level of education is becoming increasingly important for the students’ possibilities to succeed in school (Jobér, 2012, 2015). Therefore, initiatives with the ambition to empower young people must take their social and cultural background (often related to structural factors such as social class and ethnicity) in consideration and at the same time not letting such factors function as a social stigma regulating any expectations of the individual and her/his potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sweden, the school’s ability to compensate for students’ background has worsened, and the parents’ level of education is becoming increasingly important for the students’ possibilities to succeed in school (Jobér, 2012, 2015). Therefore, initiatives with the ambition to empower young people must take their social and cultural background (often related to structural factors such as social class and ethnicity) in consideration and at the same time not letting such factors function as a social stigma regulating any expectations of the individual and her/his potential.…”
Section: Discussionmentioning
confidence: 99%
“…To accomplish this, Jobér (2012, 2015) has stressed that it is important to empower children from socially disadvantaged homes, i.e., by supporting toll-free school activities. Furthermore, it is important to regard talent not as an essential or static quality of the individual, but as something that can be created and encouraged with the right pedagogical tools.…”
Section: Discussionmentioning
confidence: 99%
“…As Foucault (1980) argues, power relations are the precondition for our subjectivities and not only do they make us submit to certain norms, they also make subjectivities possible. For example, Anna Jobér (2012) has shown that students who are unaccustomed to scientific/ academic discourse (in her case, students from working-class backgrounds) can find it difficult to decode the activities in the science classroom (such as, what is expected when participating in a discussion). Consequently, providing clearly framed activities could make certain school science subjectivities possible, that otherwise would be inaccessible.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, any learning situation will also involve socialisation (Roberts and Ö stman 1998). In studies of science and technology education much focus has been placed on such socialisation processes, in particular in terms of which students are more easily socialised into the knowledge, norms and values of the disciplines and which students that are struggling and/or left outside, highlighting, for example, masculinity (Archer, DeWitt and Willis 2014), femininity (Brickhouse and Potter 2001), or social class (Jobér 2012). To at least some degree, such research has often conceptualised power (implicitly or explicitly) as structural, focusing on how different axes of power intersect with people's identity constitutions.…”
mentioning
confidence: 99%
“…Dessa bygger på rationalitet och effektivitet, vilket har lett till att människan har förlorat kontrollen över den. 59 Elluls beskrivning kan tolkas som att det är tekniken som skapar samhällsförändringarna och inte tvärtom, medan Winner och Mumford anser att trots att vi inte kan förutse vilka konsekvenser teknikutveckling får, är det ändå människan som sitter vid rodret. En sådan tekniksyn går att koppla till den tidigare nämnda diskussionen om huruvida tekniken är värdeneutral eller ej.…”
Section: Teknisk Viljaunclassified